(untitled) (Res Medica, 2014)
• Medical Teaching in Edinburgh during the 18th and 19th centuries, Matthew H. Kaufman, The Royal College Surgeons of Edinburgh 2003 • Medical Microbiology – Third Edition, Cedric A Mims (Editor)